Penggunaan Media dalam Pendidikan Jasmani Olahraga dan Kesehatan di Sekolah Menengah Pertama Negeri Se Kecamatan Plered Kabupaten Purwakarta - Muhammad Fauzul Muzammil; Rizki Aminudin; wanto wanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine how high the use of media in physical education, sports and health in State Junior High Schools in Plered District, Purwakarta Regency. This research is quantitative descriptive. The method used in this research is a survey method, the instrument is a questionnaire. The subjects in this study were all teachers of physical education, sports and health at the Se State Junior High School, Plered District, totaling 12 people. The data analysis technique used quantitative descriptive analysis which was presented in the form of percentages. The results of this study indicate that the use of learning media for physical education, sports and health in State Junior High Schools, Plered Subdistrict, Purwakarta Regency is in the very high category of 1 person or 8.33%, 2 people or 16.67% high, 5 people or 41.67%, low 3 people or 25.00%, and very low 1 person or 8.33%.